2017
DOI: 10.1016/j.jcv.2017.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genomic drift of influenza PCR tests

Abstract: Strain-associated assay performance variation is known to occur with other Flu test methods; hence, it is not surprising that such variation would be observed with molecular tests. Careful monitoring and reporting for strain-associated variances are warranted for all test methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The comparative study on FilmArray RP and Verigene RV þ reported that the sensitivity and specificity of FilmArray RP was equivalent to Verigene RVþ [17]; however, another study reported that the sensitivity of FilmArray RP in detecting Influenza virus was higher than that of Verigene [18]. A comparative study on FilmArray RP and GeneXpert (Xpert Flu) for the detection of Influenza virus reported that the positive predictive value for FilmArray RP was almost the same as that of Xpert Flu (FilmArray RP, 98.3% and Xpert Flu, 100%, respectively) [19]. Furthermore, a previous study on FilmArray RP and GeneXpert (Xpert Flu/RSV XC) for the detection of Influenza virus and Respiratory syncytial virus reported that the sensitivity and specificity of FilmArray RP were equivalent to those of the Xpert Flu/RSV XC) [20].…”
Section: Discussionmentioning
confidence: 99%
“…The comparative study on FilmArray RP and Verigene RV þ reported that the sensitivity and specificity of FilmArray RP was equivalent to Verigene RVþ [17]; however, another study reported that the sensitivity of FilmArray RP in detecting Influenza virus was higher than that of Verigene [18]. A comparative study on FilmArray RP and GeneXpert (Xpert Flu) for the detection of Influenza virus reported that the positive predictive value for FilmArray RP was almost the same as that of Xpert Flu (FilmArray RP, 98.3% and Xpert Flu, 100%, respectively) [19]. Furthermore, a previous study on FilmArray RP and GeneXpert (Xpert Flu/RSV XC) for the detection of Influenza virus and Respiratory syncytial virus reported that the sensitivity and specificity of FilmArray RP were equivalent to those of the Xpert Flu/RSV XC) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of the Cepheid® Xpert Flu Assay can also vary according to genetic drift resulting in different seasonal influenza strains (Stellrecht et al, 2017). Sensitivity of the Cepheid® Xpert Flu Assay was 85.2%, with different limits of detection depending on strain.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of the Cepheid® Xpert Flu Assay was 85.2%, with different limits of detection depending on strain. Thus, it is recommended that strain-associated variances should be carefully monitored for the Cepheid® Xpert Flu Assay (Stellrecht et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the Roche cobas Liat showed greater sensitivity than the reference rtRT-PCR and was superior when testing low-positive samples (C T values of Ͼ30), despite being performed by nonlaboratory personnel. In this same study, it was determined that a mutation in the circulating H3N2 strains in the 2014 to 2015 season resulted in false negatives in the Prodesse ProFluϩ reference test, the Roche cobas Liat, Cepheid Xpert Flu, and other NAAT (35). However, more false negatives were seen with Prodesse ProFluϩ than with the cobas Liat.…”
Section: Nucleic Acid Detection By Molecular Amplification Assays Formentioning
confidence: 98%
“…As with other diagnostic testing for viruses, molecular assays have been shown to be vulnerable to genomic drifts and shifts, leading to performance variation from year to year. In 2014 to 2015, decreased sensitivity was reported with multiple commercial molecular assays, including the Cepheid GeneXpert Flu and Roche cobas Liat, for several clades of the 3C genetic group of influenza A H3N2 compared to that for archived virus from previous years (35). This led to improvements in the tests, including the use of two influenza A virus targets in Cepheid Xpert Xpress.…”
Section: Nucleic Acid Detection By Molecular Amplification Assays Formentioning
confidence: 99%